Exploration of the clinical prognostic model of BRCA based on PCAT7 - Zhang, Zhi; Xiang, Chaocheng; Chen, Tong; Ma, Aimin; Wang, Xu; Li, Jiaying; Chen, Yixuan; Huang, Chengyu; Li, Ting; Wu, Danmei; Mo, Steven; Li, Dequan (Frontiers in Oncology, 2025)
PurposeBreast cancer (BRCA) is the most common cancer in women. Overexpression of long non-coding RNA Prostate cancer-associated transcript 7 (PCAT7) in BRCA was correlated with an unfavorable prognosis. Consequently, investigating the function and prognostic significance of PCAT7 in BRCA has become imperative.MethodsThis study used BRCA data from the Cancer Genome Atlas (TCGA) as a training cohort to evaluate the prognostic potential of PCAT7. In addition, luminal A, luminal B, HER2, and basal like triple-negative breast cancer samples were collected clinically to verify the expression of PCAT7. Meanwhile, differentially expressed genes (DEGs) related to PCAT7 were identified. Subsequently, weighted gene co-expression network analysis (WGCNA) was used to identify abnormal regulatory modules of PCAT7 co-expressed genes in BRCA. Furthermore, we used enrichment analysis to evaluate the distribution patterns of genes. We constructed a clinical indicator scoring model based on PCAT7 based prognosis-related genes, followed by correlation analyses to study the relationship between clinical indicators based on PCAT7 expression and immune cell infiltration, immune checkpoint-related genes, and tertiary lymphoid structure marker genes. Pivot analysis based on a hypergeometric approach was used to identify lncRNAs, TFs and RBPs that regulate the set of prognosis-related genes to explore drug targets.ResultsThe results showed that PCAT7 was significantly high expression in BRCA, and patients with high expression of PCAT7 had poor prognosis. IHC further confirmed that PCAT7 was significantly overexpressed in BRCA samples of different subtypes, suggesting that PCAT7 has diagnostic potential in BRCA. Meanwhile, a total of 28,892 DEGs and 954 DEmiRNAs were continuously upregulated or downregulated. The most relevant module genes associated with PCAT7 are significantly enriched in immune and cancer-related pathways. PCAT7-based models and model genes were significantly associated with multiple immune checkpoint-related genes and tertiary lymphoid structure marker genes. In addition, PCAT7 is associated with the inhibition of immune cell infiltration.ConclusionWe found that the clinical score of PCAT7 is significantly correlated with the prognosis of BRCA patients, suggesting that PCAT7 is a useful biomarker.